Literary & historical aspects of Tarikh-e-Rashidi (Eurasian Journal of Philology Science and Education, 2016)
‘Tarikh-e-Rashidi’ is a book written in Persian by the ruler of Kashmir, Mirza Haider Dughlat. The writer of the book was the cousin of Babur, the founder ofMughal dynasty in Indian subcontinent in the first half of the 16th century AD. This book which is originally based on the political history of Mughals and Turks is considered as one of the best master pieces of literary classic also because ofits special style of narrating and writing. Besides the political and diplomaticevents of his own time, he likes to talk about several different things like culture, weather, literature, great people of his time and tribe as well as many otherdifferent topics and thus keeps his book before the readers more than a book ofpolitical history only. The language used in writing of this book is also a matter of attraction for being so eloquent & charming that gives the literary colour tothe history events. The real aim of producing this research paper is to catch theeyes of the academicians, historians of the Turkish world, researchers, social scientists etc. over the book “Tarikh-e-Rashidi” of Mirza Haider Dughlat to pertain an academic exploration of this book that can enrich the Turkish historyby revealing astonishing fact hiding in itself. The present research paper is anattempt to emphasize the literary aspects and the language used in the writing ofthis book besides sketching its historical aspects as these two are the majorcharacteristics of the book which were less discussed & researched yet.
Keywords: Babur; Mirza Haider Dughlat; Mughal; Persian; «Tarikh-e-Rashidi»